1991
DOI: 10.1002/ijc.2910470720
|View full text |Cite
|
Sign up to set email alerts
|

Molecular abnormalities in the expression of HLA class-I antigens by melanoma cells

Abstract: Testing of a panel of cultured human melanoma cells with radiolabelled anti-HLA-class4 monoclonal antibodies (MAbs) in a binding assay has shown lack of reactivity of FO-I and SK-MEL-33 cells and low reactivity of SK-MEL-I9 cells. SDS-PAGE analysis of the components immunoprecipitated from the 3 intrinsically radiolabelled melanoma cell lines by antibodies to the 2 subunits of HLA-class4 antigens has not detected p2-p in the immunoprecipitates from melanoma cells FO-I and SK-MEL-33 and only a low level of HLA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The mechanism of this synergistic effect by CDDP is not clear but may be secondary to drug-induced alteration of the tumor target cell membrane, rendering it more susceptible to effector cell attack. It has been postulated that one mechanism of development of tumor metastases may be immune-mediated escape or nonrecognition of tumor targets by host immune cells [41,42]. Indeed, an elegant study by Alexander et al [43] showed that advanced but not early stage melanoma had defective antigen-presentation capability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism of this synergistic effect by CDDP is not clear but may be secondary to drug-induced alteration of the tumor target cell membrane, rendering it more susceptible to effector cell attack. It has been postulated that one mechanism of development of tumor metastases may be immune-mediated escape or nonrecognition of tumor targets by host immune cells [41,42]. Indeed, an elegant study by Alexander et al [43] showed that advanced but not early stage melanoma had defective antigen-presentation capability.…”
Section: Discussionmentioning
confidence: 99%
“…This may explain why PBL from MSTS-5 demonstrated some lysis against PSTS-4. Down-regulation of MHC class I antigens on sarcomas may allow tumors to immunologically evade host defenses [41,42]. Some patients with HLA-A2+ disseminated melanomas that were successfully treated with ALT-cells and CY were able to demonstrate ex vivo lysis of allogeneic HLA-A2+ melanomas but not HLA-A2-melanomas [5].…”
Section: Discussionmentioning
confidence: 99%
“…ICAM‐1 is expressed by a large variety of non‐hematopoietic cells such as keratinocytes (21), and is the ligand for leucocyte function associated antigen‐1 (LFA‐1): this non‐antigen specific system is considered to be crucial in the adhesion between lymphocytes and antigen‐presenting cells, endothelial cells or target cells (22). Retinoic acid‐responsive elements have been found in the 5′‐regulatory region of the human ICAM‐1 gene (23), and RA‐induced ICAM‐1 up‐regulation on the cell surface of various cell lines has already been reported, such as human thyroid cells or melanoma cell‐lines (24–26).…”
Section: Resultsmentioning
confidence: 99%
“…reduction in class I has not been defined (40). Finally, allelic variants of TAP2 (in the rat) discriminate classes of peptides for transport thereby conferring specificity to the process of antigen presentation (5).…”
Section: Resultsmentioning
confidence: 99%